Vitro study of novel microparticle based silk fibroin scaffold with osteoblast-like cells for load-bearing osteo-regenerative applications - Parekh, Nimisha Anant; Hushye, Chandni; Warunkar, Saniya; Gupta, Sayam Sen; Nisal, Anuya (RSC Advances, 2017)
Silk Fibroin (SF) is today considered to be one of the most favorable materials for bone tissue engineering. We have prepared novel SF microparticle based 3D scaffolds, with appropriate pore size, pore interconnectivity and porosity, excellent mechanical properties and tunable bioresorption, while retaining the inherent biocompatibility of SF. These properties make them ideal candidates for osteoregenerative applications. Here, we report the in vitro cell viability, cell adhesion and proliferation with osetoblastic differentiation of MG 63 osteoblast-like cell line on these scaffolds. In addition, we have also modified the surface of these scaffolds using collagen type I and chitosan biopolymers. Our results show that although the SF scaffold does support in vitro cell attachment, proliferation and differentiation, this performance can be further enhanced using the surface coating approach. Also, the ALP activity and bone mineralization was found to be particularly superior in the chitosan modified scaffolds.